SOCIAL EXPERIENTIAL FEATURES OF CHILDREN SWIMMERS AND THEIR SUCCESS IN SPORT - Vojinović Jugoslav (Sport Mont, 2009)
The aim of this research was to perceive a mutual connection of social - experien- tial features of children swimmers on one hand, and their success in sport on the other hand. According to the available methods and possibilities of their application, for this research the most relevant is empirical – unexperimental method or Survey method. An access in the obtained results shows that higher education of parents leads to less suc- cess of children in swimming. One more interesting social psychological category is a connection of parents’ pleasure and sports success. Here is also a connection negative – bigger parents’ pleasure leads more rare to sports success than less parents’ satisfac- tion (33,3 % versus 48,5 % ). Probably it is being discussed about children swimmers of those parents who have more striking ambitions when the sports success of their children is concerned. Namely, their children are successful but they would like that they are mo- re successful. The reason for that attitude of those parents probably lies in the fact that all those things that they didn’t achieve in sport in their youth, they want to achieve and compensate through their children. Or vice versa, parents who are more prominently satisfied with the behaviour of their children do not have such great expectations when the success of their children in swimming is concerned. They are cheerful because their children do some sport and because they are not exposed to all those well-known temp- tations of young people today.